Inflammatory biomarkers in very preterm infants during early intravenous paracetamol administration. (October 2021) - Aikio, Outi; Härmä, Antti; Härkin, Pia; Leskinen, Markku; Valkama, Marita; Saarela, Timo; Salminen, Annamari; Hallman, Mikko
Abstract: Background: Paracetamol promotes early closure of patent ductus arteriosus (PDA), and it may affect inflammation after preterm birth. Objective: The aim of this study was to evaluate the association between paracetamol treatment and serum inflammatory biomarkers in very preterm infants with respiratory distress. Study design: The infants were randomly assigned to intravenous paracetamol or placebo during the first 4 days of life, and others received a lower dose of paracetamol unblinded. Serum samples were used for the analysis of 10 cytokines, C-reactive protein (CRP) and malondialdehyde (MDA). The impact of paracetamol on the biomarkers was evaluated, based on the levels during the early (<60 h) and the later (60–120 h) postnatal age. Results: Altogether, 296 serum samples from 31 paracetamol and 25 placebo group infants were analysed. Paracetamol had no effect on cytokine levels during the first 60 h when most induced PDA contractions took place. Later paracetamol treatment was associated with lower serum levels of several cytokines, including interleukin (IL-) 10, interferon gamma-induced protein (IP-) 10, and monocyte chemoattractant protein-1. CRP levels were lower in the paracetamol group during the early treatment. Amongst the infants who had severe morbidities, MDA was higher ( p = .045), regardless of paracetamol treatment. Conclusion: No significant differences in the cytokine levels were evident between the treatment and placebo groups. However, during early treatment, CRP levels were lower in the paracetamol group. To clarify whether this was due to a decrease in cardiopulmonary distress, or a distinct anti-inflammatory effect, requires further studies. Highlights: In preterm infants, early paracetamol constricted ductus and improved oxygenation. In present results, CRP levels tended to remain lower in the paracetamol group. Paracetamol use was also associated with lower serum levels of several cytokines. Infants with severe morbidities had higher malondialdehyde despite paracetamol. These may due to decreased cardiopulmonary distress or an anti-inflammatory effect.